2017
DOI: 10.1002/2017gl075310
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Conversion and Mixing Poleward of the Critical Latitude (an Arctic Case Study)

Abstract: The tides are a major source of the kinetic energy supporting turbulent mixing in the global oceans. The prime mechanism for the transfer of tidal energy to turbulent mixing results from the interaction between topography and stratified tidal flow, leading to the generation of freely propagating internal waves at the period of the forcing tide. However, poleward of the critical latitude (where the period of the principal tidal constituent exceeds the local inertial period), the action of the Coriolis force pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 25 publications
1
46
0
Order By: Relevance
“…Unlike freely propagating, semidiurnal modes, the diurnal topographic waves associated with the barotropic tides over the Gunnerus Bank are trapped, that is, they cannot propagate, because they are poleward of the critical latitude, and their conversion into internal waves may be important to facilitate the resonance of these modes inside the ice shelf cavity. Nonlinear and linear examples of propagating baroclinic waves at above‐critical latitudes exist (Hughes & Klymak, ; Rippeth et al, ) and comparable seasonal resonances of baroclininc waves with diurnal tides have been observed at similar configurations along the Antarctic continental slope (Jensen et al, ; Semper & Darelius, ). Idealized models that have been used to quantify the internal wave energy rely on constant geometry assumptions, which is challenging for the complex and partially unknown bathymetry around the Riiser‐Larsen Peninsula and beneath the RBIS.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike freely propagating, semidiurnal modes, the diurnal topographic waves associated with the barotropic tides over the Gunnerus Bank are trapped, that is, they cannot propagate, because they are poleward of the critical latitude, and their conversion into internal waves may be important to facilitate the resonance of these modes inside the ice shelf cavity. Nonlinear and linear examples of propagating baroclinic waves at above‐critical latitudes exist (Hughes & Klymak, ; Rippeth et al, ) and comparable seasonal resonances of baroclininc waves with diurnal tides have been observed at similar configurations along the Antarctic continental slope (Jensen et al, ; Semper & Darelius, ). Idealized models that have been used to quantify the internal wave energy rely on constant geometry assumptions, which is challenging for the complex and partially unknown bathymetry around the Riiser‐Larsen Peninsula and beneath the RBIS.…”
Section: Discussionmentioning
confidence: 99%
“…There is relatively weak tidal forcing in the Arctic, and most of the region is above the critical latitude north of which the semidiurnal lunar tide can propagate freely (Kowalik & Proshutinsky, ). Topographic waves generated over bathymetric slopes and rough topography, forced by the tides, are the main source of energy for higher tidal dissipation observed over topography (Holloway & Proshutinsky, ; Kowalik & Proshutinsky, ; Luneva et al, ; Padman et al, ; Rippeth et al, ). Sea‐ice cover is present for most of the year and acts as a buffer to wind‐driven momentum input to the upper ocean; further, internal wave energy can be dissipated under sea ice (Morison et al, ; Pinkel, ).…”
Section: Mixing and Stirring In The Arctic Oceanmentioning
confidence: 99%
“…Rippeth et al () also detected elevated turbulence across rough Arctic continental shelf breaks that were linked to the tide. Unique environmental factors in high‐latitude oceans, including the suppression of freely propagating linear internal tides poleward of the critical latitude, the importance of tidal energy conversion to nonlinear waves (Rippeth et al, ), and the insulating effects of sea ice cover, are further expected to impose regional and seasonal limitations on internal wave generation, evolution and, ultimately, wave‐driven mixing. Previous studies, including a mixture of both direct turbulence measurements and finescale estimates of wave‐driven turbulence, have found that the turbulent kinetic energy dissipation rate, ε , and associated eddy diffusivity, κ , can each span 2 to 4 orders of magnitude in localized Arctic regions (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Rippeth et al (2015) also detected elevated turbulence across rough Arctic continental shelf breaks that were linked to the tide. Unique environmental factors in high-latitude oceans, including the suppression of freely propagating linear internal tides poleward of the critical latitude, the importance of tidal energy conversion to nonlinear waves (Rippeth et al, 2017), and the insulating effects of sea ice cover, are further expected to Table 1 Summary of Dissipation Rate, , Mixing Rate, , and Heat Flux, F H , Results From Previous Turbulent Mixing Studies Wijesekera et al (1993) Yermak Plateau 10 −10 -10 −8 Fine Sundfjord et al (2007) Barents Sea 10 −8 -10 −6 10 −5 -10 −3 0.3-50 Micro Fer and Sundfjord (2007) Barents Sea 10 −8 -10 −6 10 −4 -10 −3 10-20 Micro Lenn et al (2009) East Siberian slope 10 −10 -10 −9 10 −6 -10 −4 0.01-5 Micro Fer (2009) Amundsen Basin 10 −9 -10 −7 10 −6 -10 −4 0-0.5 Micro Fer et al (2010) Yermak Plateau 10 −9 -10 −7 10 −5 -10 −4 −15-15 Micro/fine Bourgault et al (2011) Amundsen Gulf 10 −9 -10 −7 10 −6 -10 −3 Micro Lenn et al (2011) Laptev Sea 10 −6 -10 −3 10 −6 -10 −3 Micro Guthrie et al (2013) Central Arctic 10 −6 -10 −4 −2-2 Micro/fine /Canada Basin Rippeth et al (2015) Circumpolar shelves 10 −9 -10 −7 0.05-50 Micro /Canada Basin Kawaguchi et al (2016) Chukchi Plateau 10 −10 -10 −8 O(1) Micro/fine…”
Section: Introductionmentioning
confidence: 99%